2018
DOI: 10.3390/ma11122557
|View full text |Cite
|
Sign up to set email alerts
|

A Mini Review: Recent Advances in Surface Modification of Porous Silicon

Abstract: Porous silicon has been utilized within a wide spectrum of industries, as well as being used in basic research for engineering and biomedical fields. Recently, surface modification methods have been constantly coming under the spotlight, mostly in regard to maximizing its purpose of use. Within this review, we will introduce porous silicon, the experimentation preparatory methods, the properties of the surface of porous silicon, and both more conventional as well as newly developed surface modification methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 68 publications
0
29
0
1
Order By: Relevance
“…Porous silicon has been found useful in a broad range of industries [4]. Numerous methods for synthesizing such materials have been reported, and the review paper by Lee et al summarizes breakthroughs and recent trends [5]. Despite extensive work, there is still a great demand for further development of advanced surface modification methods for this material.…”
Section: This Special Issuementioning
confidence: 99%
“…Porous silicon has been found useful in a broad range of industries [4]. Numerous methods for synthesizing such materials have been reported, and the review paper by Lee et al summarizes breakthroughs and recent trends [5]. Despite extensive work, there is still a great demand for further development of advanced surface modification methods for this material.…”
Section: This Special Issuementioning
confidence: 99%
“…Si can be used to make wafers of high purity without defects. These features enable Si to be a critical element for fabricating various semiconductor devices . In particular, Si is an ideal semiconductor for construction of broadband photodetectors due to its small bandgap, superior light‐trapping ability, and fast charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…These features enable Si to be a critical element for fabricating various semiconductor devices. [13][14][15] In particular, Si is an ideal semiconductor for construction of broadband photodetectors due to its small bandgap, superior light-trapping ability, and fast charge transport. Si photodetectors are commercially utilized for light photodetection in the UV to near-infrared (NIR) region.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that hydride groups are strong reducing agents that make the surface incompatible to conjugate with many biological or non-biological materials 33 . Hence, surface passivation of PSi is a critical step to stable its surface for application at biological research fields 34 . Thus, the fresh PSi samples were modified as reported in the "PSi surface modification" section.…”
Section: Resultsmentioning
confidence: 99%